FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM - HANNA CHRITIANTO YAP; FRISKA FIRNANTI (Jurnal Bisnis dan Akuntansi, 2019)
The purposive of this study is to obtain emperical evidence about the factors that influence stock market returns. The examine factors are: solvency ratio is measured by Debt to Equity Ratio; profitability ratios are measured by Return on Assets, Return on Equity, Earnings per Share, Price Earnings Ratio, and Net Profit Margin; liquidity ratio is measured by Quick Ratio; the measurement of the company's financial performance is measured by Firm Size and Residual Income. Samples in this research are manufacturing companies listed in Indonesia Stock Exchange during 2013-2016. The sample used as many as 44 companies with a total of 176 data. The results show that Return on Asset, Return on Equity, Quick Ratio, Earnings per Share, Net Profit Margin, Residual Income, Firm Size, Price Earnings Ratio, and Debt to Equity Ratio don’t have any influence toward Stock Returns.